Adverse genomic alterations and stemness features are induced by field cancerization in the microenvironment of hepatocellular carcinomas - Častven, Darko; Rössler, Stephanie (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.16231 Darko Castven, Michael Fischer, Diana Becker, Stefan Heinrich, Jesper B. Andersen, Dennis Strand, Martin F. Sprinzl, Susanne Strand, Carolin Czauderna,...
Gesehen am 03.05.2018